IMPLEMENTASI PENDIDIKAN SPIRITUAL MELALUI KITAB SYI'IR JAWI PADA KESEHATAN LANSIA DI TPQ AL-MUHIBBIN JOMBANG - Achmad Nidzomi; Ita Rahmania Kusumawati (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
Abstract: Old age is a period where there is a decline both physically and psychologically, so that at this stage a person becomes vulnerable to stress, depression, and loneliness. In addition, old age is also a phase close to death, so having a strong spirituality is very important to interpret life related to oneself, God, and fellow beings. Spirituality education becomes a form of education that can help individuals live a life with peace and tranquility. Therefore, spiritual education has a very important role, especially for those who have entered old age who are physically and psychologically vulnerable. This research uses qualitative methods with a case study approach that aims to find the extent of the impact of spiritual education on elderly mothers at TPQ Al-Muhibbin Jombang. The subjects in this study were mothers aged 60 years and over who were registered as students at TPQ Al-Muhibbin Jombang. While the object of this study is religious activities used to improve the spirituality of the elderly. The location of this research is TPQ Al-Muhibbin which is located at four points, namely (1) Cangkringrandu Perak Jombang, (2) Tambakberas Timur Tambakrejo Jombang, (3) Nglungu Tambakrejo Jombang, and (4) Bangle Dukuhklopo Peterongan Jombang. The purpose of this study was to determine the spiritual education activities used on elderly mothers and the extent of the impact of spiritual education on their mental health. After research, it was found that there are two religious activities that can improve the spirituality of the elderly at TPQ Al-Muhibbin, in the classroom and outside the classroom. Activities in class include learning to read Yanbu'a, reading short letters of the Qur'an, following assemblies of both tafsir, fiqh and shi'iran. Activities outside the classroom include participating in recitations such as the Birthday of the Prophet Muhammad (saw), the commemoration of Isro 'Mi'roj Prophet Muhammad SAW., Joint Prayer, Halal bi Halal, alms 10 Suro, orphan compensation, and visiting friends who are sick or dead